2021
DOI: 10.1126/sciadv.abe8132
|View full text |Cite
|
Sign up to set email alerts
|

Na + /Ca 2+ exchanger mediates cold Ca 2+ signaling conserved for temperature-compensated circadian rhythms

Abstract: Circadian rhythms are based on biochemical oscillations generated by clock genes/proteins, which independently evolved in animals, fungi, plants, and cyanobacteria. Temperature compensation of the oscillation speed is a common feature of the circadian clocks, but the evolutionary-conserved mechanism has been unclear. Here, we show that Na+/Ca2+ exchanger (NCX) mediates cold-responsive Ca2+ signaling important for the temperature-compensated oscillation in mammalian cells. In response to temperature decrease, N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…The previous studies revealed that expression levels of Per1 and Per2 are transiently induced by cytoplasmic Ca 2+ increase both in the SCN and peripheral cells 18 , 19 , 22 . We found that temperature decrease chronically elevates cytoplasmic Ca 2+ levels and Per1 and Per2 transcripts 18 (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…The previous studies revealed that expression levels of Per1 and Per2 are transiently induced by cytoplasmic Ca 2+ increase both in the SCN and peripheral cells 18 , 19 , 22 . We found that temperature decrease chronically elevates cytoplasmic Ca 2+ levels and Per1 and Per2 transcripts 18 (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 97%
“…We employed transcriptional reporters that express luciferase under the control of Per1 or Per2 promotor 22 . In addition, luciferase reporter of Bmal1 19 promoter was also analyzed as a negative control reporter, because the mRNA levels of Bmal1 showed no increase under lower temperature 18 . The cells were first synchronized with 1 h-pulse of 0.1 μM dexamethasone, and the medium was replaced with an air culture medium before measuring bioluminescence.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously described genetic perturbations that alter temperature compensation in animals have or may have altered the Q 10 of the encoded protein. Even in the case of pharmacological manipulations that alter temperature compensation, direct measures indicate inhibitors/antagonists can also significantly perturb the Q 10 of their targets(35) or the Q 10 has not been independently measured(31). In other cases, some gene dosage mutants in fungi that perturb temperature compensation actually exhibit phenotypes with better temperature compensation, i.e., Q 10 s closer to 1(5).…”
Section: Discussionmentioning
confidence: 99%